Studi Tentang Penerapan Golden Handcuffs: Pinjaman Karyawan dari Perusahaan Sebagai Cara untuk Meminimalkan Turnover - Bahrul Ulum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Abstract: High employee Turnover rates pose a serious challenge in human resource management, particularly in the competitive banking sector, such as Bank XYZ. One strategy used to retain employees is the implementation of a golden handcuff policy, which provides long-term financial incentives such as low-interest loans. This study aims to determine the effectiveness of this policy in minimizing employee Turnover by considering three key dimensions: financial, social, and business processes. The method used in this study is the Analytical Hierarchy Process (AHP), which enables systematic decision-making through weighting criteria and sub-criteria. A hierarchical structure was developed with the primary goal of minimizing Turnover, with three main criteria (financial, social, and business processes), nine sub-criteria, and two policy alternatives: maintaining or eliminating the golden handcuff policy. Data were obtained through paired questionnaires administered to HR experts and managers at Bank XYZ. The results of this study are expected to identify the dominant factors influencing employee retention decisions and provide data-driven strategic recommendations to management in designing effective and sustainable retention policies. Keywords: Decision Making, Employee Turnover, Golden Handcuff, Low Interest Loans, Retention Strategy